Pengaruh Promosi, Ketersediaan Produk Dan Penggunaan Paylater Terhadap Impulse Buying Pada E-Commerce Shopee: (Studi Kasus Pada Mahasiswa Prodi Manajemen Angkatan 2020 Universitas Bhayangkara Jakarta Raya) - Amelia Putri, Shinta; Pantjolo Giningroem, Dewi Sri Woelandari; Pitoyo, Bayu Seno (OGZ Research & Publishing, 2024)
The purpose of this research is to identify and analyze the factors influencing impulsive buying behavior, providing insights to businesses on effective strategies to enhance impulsive purchases in their market. This study employs a quantitative method, utilizing data collection through questionnaires implemented in a survey. The number of respondents involved in this research reaches 200 individuals. The data analysis approach in this study utilizes the multiple linear regression analysis method, with the application of SPSS software. The findings of the research indicate that promotions, product availability, and the utilization of pay-later services significantly influence impulsive buying occurrences.